Aplikasi Estimasi Biaya Bangunan Gedung Berdasarkan Analisa Harga Satuan Pekerjaan Berbasis Macro Excel - Lendra Lendra; Robby Robby; Frediyantoni F. Adji; Muhammad Faqqih (Jurnal Aplikasi Teknik Sipil, 2023)
Estimating construction project costs is usually done manually; it takes a long time, and the more comprehensive the estimate, the more manual calculations must be performed, increasing the risk of human errors. This study aims to make a building cost estimation application using the 2022 Work Unit Price Analysis (AHSP), based on excel macros, so that cost estimates become more accurate and efficient. The first step is to design the framework and application design and then analyze the database requirements. The second step: database creation and application interface design. The third step: testing, validation, and verification on two building projects in 2022. The estimation results of this application are very accurate and efficient, where the total cost is Rp. 382,998,432.00, while the bid price is Rp. 383,000,000.00. There is a difference in calculation costs compared to the bid price, which is Rp. 1,568.00 (0.00041%).